2016
DOI: 10.1016/j.renene.2016.05.092
|View full text |Cite
|
Sign up to set email alerts
|

A novel control method to maximize the energy-harvesting capability of an adjustable slope angle wave energy converter

Abstract: . (2016) A novel control method to maximize the energy-harvesting capability of an adjustable slope angle wave energy converter. Renewable Energy, 97. pp. 518-531. Permanent WRAP URL:http://wrap.warwick.ac.uk/87072 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Moreover, an oil hydraulic PTO was directly driven by a heaving buoy under regular waves in the experiments, which verified the proposed mathematical model [22]. Compared with a WEC with a vertical fixed strut, an adjustable slope angle heaving-buoy WEC was tested in regular waves and found to provide 5% increase in overall efficiency [23].…”
Section: Introductionsupporting
confidence: 62%
“…Moreover, an oil hydraulic PTO was directly driven by a heaving buoy under regular waves in the experiments, which verified the proposed mathematical model [22]. Compared with a WEC with a vertical fixed strut, an adjustable slope angle heaving-buoy WEC was tested in regular waves and found to provide 5% increase in overall efficiency [23].…”
Section: Introductionsupporting
confidence: 62%
“…On the one hand, some studies have proposed the use of neural networks to find the optimal parameters for impedance-matching control on a time-averaged basis [21], thus being readily applicable to the centralised control of multiple WECs [22]. On the other hand, other works have focused on real-time control [19,20,23], exploiting the capability of neural networks to handle the predicted wave elevation over a future time horizon, similar to MPC. The main advantage of machine learning models for the system identification of WECs is that the same method can be used for different WEC technologies and is potentially adaptive to changes in the system dynamics, e.g., to subsystem failures or biofouling.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, on the west side of Sicily, Iuppa et al 21 evaluated the performance of several wave energy conversion devices and showed that only by resizing the devices based on different wave climates can a large capacity factor be obtained. In 2016, Tri et al 22 used a learning vector quantitative neural network algorithm and introduced a novel control approach to maximize the output energy of an adjustable slope angle wave energy converter with an oil-hydraulic power take-off and performed simulations of the control system with irregular waves to confirm the applicability of the approach in practice. In 2017, Zheng et al 23 of Tsinghua University used the linear potential flow theory and the theory of wave diffraction and radiation to study the hydrodynamic characteristics of a raft-type, wave-powered desalination device through numerical simulations and theoretical analyses and discussed the influence of several parameters on the power capture efficiency of the wave energy.…”
Section: Introductionmentioning
confidence: 99%